2020
DOI: 10.3389/fmicb.2020.01677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Pollution and Compost Amendment on the Root Microbiome of a Metal Tolerant Poplar Clone

Abstract: Until recently, many phytoremediation studies were focused solely on a plants ability to reclaim heavy metal (HM) polluted soil through a range of different processes, such as phytoextraction and phytostabilization. However, the interaction between plants and their own rhizosphere microbiome represents a new research frontier for phytoremediation. Our hypothesis is that rhizomicrobiome might play a key role in plant wellness and in the response to external stimuli; therefore, this study aimed to shed light the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…Furthermore, excess levels of Zn in soil also contribute to the inhibition and alteration of soil microorganisms ( Olaniran et al, 2013 ), due to its bioavailability in the form of ionic Zn and as part of organo-metallic complexes, which have been previously determined ( Pueyo et al, 2004 ; Anju and Banerjee, 2011 ; Fedotov et al, 2012 ; Agnieszka et al, 2014 ; Kim et al, 2015 ; Baran et al, 2018 ). Therefore, efficient methods of heavy metal remediation are crucial for the alleviation of Zn toxicity in order to preserve soil microorganisms and their biodiversity, as well as plant and human health ( Guarino et al, 2020 ).…”
Section: Zinc Toxicitymentioning
confidence: 99%
“…Furthermore, excess levels of Zn in soil also contribute to the inhibition and alteration of soil microorganisms ( Olaniran et al, 2013 ), due to its bioavailability in the form of ionic Zn and as part of organo-metallic complexes, which have been previously determined ( Pueyo et al, 2004 ; Anju and Banerjee, 2011 ; Fedotov et al, 2012 ; Agnieszka et al, 2014 ; Kim et al, 2015 ; Baran et al, 2018 ). Therefore, efficient methods of heavy metal remediation are crucial for the alleviation of Zn toxicity in order to preserve soil microorganisms and their biodiversity, as well as plant and human health ( Guarino et al, 2020 ).…”
Section: Zinc Toxicitymentioning
confidence: 99%
“…Thus, zinc is a constituent of many proteins, it is also an enzyme cofactor and is fundamental for optimum plant growth and development. However, at high concentrations in the soil, Zn is phytotoxic, and plants that accumulate it through root absorption or deposition pose a health risk to consumers [ 5 ]. Nickel is an essential micronutrient required for the growth of higher plants.…”
Section: Introductionmentioning
confidence: 99%
“…As an important component of the soil ecosystem, rhizosphere microbes are ubiquitously implicated in the regulation of plant growth and remediation of contaminated soil. A number of studies have shown that rhizospheric microbes play important roles in the corrosion of metal in soils and heavy metal tolerance in plants (Y. Chen et al, 2018; Guarino et al, 2020; Huang et al, 2021; Jiao et al, 2019). For example, three common legume plants showed clear succession and resilience patterns of the soil microbiome in response to inorganic and organic contaminants in the study of Jiao et al (Jiao et al, 2019), and they found that different legume plants displayed stronger soil microbiome taxonomic selection processes that were helpful for the growth of plants with metal tolerance ability.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that rhizospheric microbes play important roles in the corrosion of metal in soils and heavy metal tolerance in plants (Y. Chen et al, 2018;Guarino et al, 2020;Huang et al, 2021;Jiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%